Using Augmented Reality Application to Reduce Time Completion and Error Rate in PC Assembly - Safiani Osman; Danakorn Nincarean Eh Phon; Nurul Aswa Omar; Mohd Rustam Mohd Rameli; Najua Syuhada Ahmad Alhassora; Taufik Gusman (JOIV : International Journal on Informatics Visualization, 2020)
In the present context of globalization, the demand for assembly skill has increased and play an essential role in today’s industry. The traditional assembly instruction, face-to-face and manual instruction, may contain unimportant information that can result in misinterpretation, which in turn may increase the number of error and takes longer time to complete the task. A new technology (AR) claims to increase the efficiency of assembly task by directly visualizing computer generated 3D information in the real environment. Therefore, this study aims to determine the impact of AR on the time of task completion and the number of error made during the assembly task. The comparative user study was quantitative involving 18 users divided into either AR group or traditional group performing a pc assembly task. Statistical analysis revealed that the time of completion and error rate for two different group is statistically significant. The findings showed that the use of AR application has resulted in decreasing the number of error made and shorten the time to complete the task than the traditional instructional manual in assemble a pc. Considering these result, it can conclude that augmented reality application is an effective and beneficial tool to be applied in assembly and education.